The role of microorganisms in shaping the nectar chemistry of mānuka plants (Leptospermum scoparium) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Ecology at Massey University, Manawatū, New Zealand - Bresciano Kauffman, Jorge Carlo (Massey University, 2022)
Mānuka (Leptospermum scoparium) honey is one of the main export products from New Zealand. The distinctiveness of this honey comes from the floral nectar, which possesses dihydroxyacetone, a carbohydrate with UV protection capabilities, which converts to methylglyoxal, usually during the honey maturation process. Methylglyoxal gives mānuka honey its biological activity (antimicrobial and antioxidant properties) and is often used as a quality marker. While it is acknowledged that microorganisms play an important role in plant ecology, their abundance and impact on nectar chemistry remain understudied. Microorganisms can arrive in the nectar by pollinator activity or through the phloem and can change nectar chemical properties. This thesis aims to fill a gap in the knowledge of the microbial diversity of the nectar; the impact of pollinators in the microbial nectar community, and the effect of bacteria on dihydroxyacetone production and sugar content in mānuka nectar. To achieve this aim, a combination of metagenomics, bacterial cultivation, chemical analyses, and biological in vivo and in vitro assays was conducted. The results show that mānuka nectar bacterial communities were dominated by Pseudomonadales, followed by Rhizobiales, Sphingomonadales, Corynebacteriales, Baccillales, Enterobacteriales, Xanthomonadales, Clostridiales, and Lactobacillales, while nectar fungi communities were dominated by Microbotryomycetes, Dothideomycetes, Malasseziomycetes, Sordariomycetes, and Ustilaginomycetes. When comparing bagged (pollinator restricted) and unbagged (with pollinator access) flowers, a bioinformatic and statistical analysis showed the bacterial community did not differ in community composition. In contrast, the fungal community was affected by pollinator visitation, and by plant genotype. The inoculation of an important functional bacterial Pantoea agglomerans, that previously was identified as a biomarker for the bacterial community, determined by linear discriminant analysis and network analysis, showed a significant increase in DHA using natural nectar under the laboratory. However, P. agglomerans in vivo inoculation did not change the composition of the main nectar sugars, suggesting that bacterial inoculation can maximize important plant metabolites like DHA, with minor disruption to nectar sugar content. The cultivable bacterial community differed little from the main groups found through metabarcoding, meaning the stability or structure of a core bacterial community in the nectar can be maintained through cultivation. This thesis fills an important gap in the knowledge of microbial ecology of mānuka plants and provides insights into how to manipulate key bacteria to increase DHA nectar content.
Keywords: Leptospermum scoparium; Microbiology; Nectar; Composition; New Zealand; 310802 Plant biochemistry